High-strength polyurethane based on carbon dioxide polycondensation and preparation method thereof
By condensing carbon dioxide and diol to form a polycarbonate diol soft segment, and combined with isocyanate and bio-based chain extender, high-strength polyurethane materials are prepared, solving the problems of low carbon dioxide utilization and bio-based content of existing materials, and achieving high-strength and excellent mechanical properties of polyurethane materials.
Patent Information
- Application Number
- CN202411890228.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing polycarbonate polyurethane materials have low carbon dioxide utilization and low biobase content, resulting in low resource utilization and poor environmental protection performance.
High-strength polyurethane material is prepared by direct condensation of carbon dioxide and diol into a polycarbonate diol soft segment, and combined with isocyanate and bio-based chain extender. This method is simple in process and can significantly improve the utilization rate of carbon dioxide and biomass resources.
It achieves high strength and excellent mechanical properties of polyurethane materials, and the tensile strength can reach more than 80MPa, which broadens the application range of polyurethane elastomer materials, while improving the environmental protection performance and resource utilization efficiency of the materials.
Smart Images

Figure CN119875058A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane materials, and in particular relates to a high-strength polyurethane based on carbon dioxide polycondensation and a preparation method thereof. Background Art
[0002] Polyurethane is a large class of polymers with a main chain containing urethane bonds (-NHCOO-) generated by isocyanates and polyols. These polymers have a variety of structures and components. In 1937, researchers discovered polyurethane through the addition reaction of polyester diols and diisocyanates. Due to the simple preparation process, high reactivity of raw materials and mechanical properties that can be adjusted over a wide range, polyurethane materials are widely favored by the market. However, most of the raw materials in the polyurethane industry currently rely on the exploitation of petroleum resources, and the source of raw materials is limited by non-renewable resources, so it is necessary to find alternative raw materials.
[0003] One of the most important performance indicators for evaluating polyurethane materials is its mechanical properties, which often depend on the combined effect of soft segments and hard segments. The soft segment refers to the long-chain alcohol group in the polyurethane molecular chain. Its existence makes the polyurethane material flexible and stretchable, and can improve the tear resistance and wear resistance of the polyurethane material. The hard segment refers to the diisocyanate or diol group in the isocyanate molecular chain, which can determine the hardness, strength and wear resistance of the polyurethane, and increase the chemical stability and mechanical properties of the polyurethane material. In recent years, people have paid extensive attention to improving the environmental protection of polyurethane materials by introducing bio-based monomers into them, but often ignore the final mechanical properties of polyurethane materials, which affects their practicality. Therefore, it is an effective way to achieve sustainable development not only to pay attention to the green source of monomers, but also to improve the mechanical strength of polyurethane materials.
[0004] Carbon dioxide is a non-toxic, harmless, low-cost and widely available renewable resource, and has gradually developed into a hot chemical raw material. Polycarbonate diols can be prepared by direct polymerization of carbon dioxide and diols. The chain segment flexibility is adjustable and easy to scale production, which is very suitable for the soft segment in polyurethane synthesis. Therefore, actively exploring and developing the direct polycondensation of carbon dioxide and diols to synthesize polycarbonate diol soft segments and prepare high-performance polyurethane materials is an ideal material that conforms to the development trend of green and low-carbon.
[0005] The invention patent application with application number CN202110958430.4 discloses a polycarbonate polyurethane elastomer sealing material and its preparation method and application. PCDL is reacted with toluene diisocyanate and chain extender trimethylolpropane to synthesize a polycarbonate polyurethane elastomer sealing material with better mechanical properties, hydrolysis resistance, heat resistance, oxidation resistance, friction resistance and chemical resistance than traditional polyurethane materials. The invention patent application with application number CN202310780358.X discloses a polyurethane rubber and its preparation method, using polycarbonate polyurethane to replace traditional polyester, polyether or polycaprolactone polyurethane, so that the rubber has better performance. Although the polycarbonate diol soft segment used in the polycarbonate polyurethane elastomer in the above-mentioned existing scheme is obtained by polymerization of DMC or DPC with diols, it still has problems such as low utilization rate of carbon dioxide and low bio-based content. Therefore, it is a technical problem to be solved urgently to develop a class of high-strength polyurethane based on carbon dioxide polycondensation to improve the utilization rate of biomass resources. Summary of the invention
[0006] In order to solve the technical problems of low carbon dioxide utilization rate and low bio-based content of polycarbonate polyurethane materials in the prior art, the present invention provides a type of high-strength polyurethane based on carbon dioxide condensation and a preparation method thereof. The method has a simple process and can significantly improve the utilization rate of carbon dioxide and biomass resources.
[0007] In a first aspect, the present invention provides a type of high-strength polyurethane based on carbon dioxide polycondensation, which comprises the following raw material components by mole fraction: The sum of the polycarbonate diol and the chain extender is 100 parts; 100 parts of diisocyanate; Catalyst 0.05-0.5 parts; Wherein, the chain extender is 25-50 parts; The chain extender structure is: or
[0008] Among them, n=0,1.
[0009] Furthermore, the diisocyanate is selected from at least one of hexamethylene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), lysine diisocyanate, 1,4-cyclohexane diisocyanate, and toluene diisocyanate (TDI), preferably IPDI.
[0010] Furthermore, the catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, stannous isooctanoate, phosphoric acid, oleic acid, adipic acid, and triethylamine, preferably dibutyltin dilaurate.
[0011] Furthermore, the number average molecular weight of the polycarbonate diol is 800-2000 g / mol, preferably 2000 g / mol.
[0012] Furthermore, the molar ratio of the polycarbonate diol to the chain extender is (1-3):1, preferably 1:1.
[0013] In a second aspect, the present invention provides a method for preparing a high-strength polyurethane based on carbon dioxide polycondensation, comprising the following steps: S1, adding polycarbonate diol into a reactor, and heating and dehydrating under vacuum; S2, under the protection of inert gas, adding diisocyanate, catalyst and solvent, reacting to obtain prepolymer, S3. Under the protection of inert gas, the chain extender and the solvent are mixed and added into a reactor to carry out a chain extension reaction; thereafter, the mixture is poured, solidified and dried to obtain the high-strength polyurethane based on carbon dioxide polycondensation.
[0014] Furthermore, the solvent is selected from at least one of toluene, xylene, acetone, dichloromethane, chloroform, tetrahydrofuran, acetonitrile, ethyl acetate, butyl acetate, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, preferably N,N-dimethylformamide and N,N-dimethylacetamide.
[0015] Furthermore, the amount of the solvent added in step S2 is 3-10 times the amount of the diisocyanate substance; and the amount of the solvent added in step S3 is 30-100 times the amount of the diisocyanate substance.
[0016] Furthermore, in step S1, the vacuum degree is less than 200 Pa, the heating temperature is 90-120°C, and the dehydration time is 1-6 hours, preferably 2-3 hours.
[0017] Further, in step S2, the heating temperature is 80-100°C, and the prepolymerization time is 1-3h.
[0018] Furthermore, in step S3, the heating temperature of the chain extension reaction is 50-100° C., and the reaction time is 4-12 hours; the pouring and curing temperature is 80-120° C., and the pouring and curing time is 24-48 hours.
[0019] Furthermore, the number average molecular weight of the polycarbonate diol is 800-2000 g / mol.
[0020] Furthermore, the polycarbonate diol is prepared by the following method: R1. Dehydration polycondensation of carbon dioxide and aliphatic diol: aliphatic diol, organic base catalyst and carbodiimide compound are placed in a pressure-resistant autoclave, heated to 130° C. in a carbon dioxide atmosphere at 1 MPa for dehydration polycondensation, reacted for 6-24 hours, and then post-treated to obtain oligocarbonate; R2, melt polycondensation of oligocarbonate: the oligocarbonate prepared in step R1 and the polycondensation catalyst are placed in a reactor, heated to 160-230° C. under an inert gas atmosphere and mechanical stirring, and then the pressure is reduced to 50-200 Pa for melt polycondensation, and the reaction is carried out for 0.5-1 h to obtain the polycarbonate diol; Furthermore, the structural formula of the aliphatic diol is:
[0021] Among them, n=2, 3, 4, 5.
[0022] Furthermore, the organic base catalyst is selected from at least one of N,N,N',N'-tetramethylethylenediamine (TMEDA), 4-dimethylaminopyridine (DMAP), 4-pyrrolidinylpyridine (PPY), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD), 1,1,3,3-tetramethylguanidine (TMG), and 2-tert-butyl-1,1,3,3-tetramethylguanidine (t-Bu-TMG).
[0023] Furthermore, the condensing agent is selected from at least one of dicyclohexylcarbodiimide and diisopropylcarbodiimide.
[0024] Furthermore, the polycondensation catalyst is at least one of sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide, lithium acetylacetonate, zirconium acetylacetonate, and cesium carbonate.
[0025] Furthermore, the mass ratio of the low molecular weight prepolymer to the polycondensation catalyst is 1:(0.001-0.005).
[0026] Furthermore, the post-treatment method of the low molecular weight prepolymer in step R1 is: adding an appropriate amount of solvent to fully dissolve the low molecular weight prepolymer at -20-0°C, filtering, acid washing the filtrate, drying, rotary evaporation and vacuum drying.
[0027] In a third aspect, the present invention provides a method for preparing a high-strength polyurethane bio-based chain extender, comprising the following steps: T1, adding β-alanine methyl ester hydrochloride, an acid binding agent and a first solvent into a reactor, slowly adding a diacyl chloride solution dropwise at -10-10°C, and refluxing at 25-60°C to generate the corresponding dicarboxylic acid dimethyl ester; T2, adding the dimethyl dicarboxylate prepared in step T1, hydrazine hydrate and the second solvent into a reactor, and reacting under reflux at 70-100° C. to generate the corresponding dihydrazide, and obtaining the bio-based chain extender after separation and purification.
[0028] Furthermore, the diacyl chloride is selected from at least one of oxalyl chloride, succinyl chloride and 2,5-furandicarboxylic acid chloride.
[0029] Furthermore, the molar ratio of β-alanine methyl ester hydrochloride, diacyl chloride and acid binding agent in step T1 is 2: (0.8-1.2): (3.6-4.4).
[0030] Furthermore, the molar ratio of the dimethyl dicarboxylate and the hydrazine hydrate in step T2 is 1:(2.5-4).
[0031] Furthermore, the acid binding agent in step T1 is selected from at least one of triethylamine and pyridine.
[0032] Furthermore, the first solvent described in step T1 is selected from at least one of dichloromethane, chloroform, tetrahydrofuran, acetonitrile, acetone, methyl tert-butyl ether, and 1,4-dioxane, preferably dichloromethane or tetrahydrofuran.
[0033] Furthermore, the second solvent described in step T2 is selected from at least one of methanol, ethanol, isopropanol, n-butanol, and tert-butanol, preferably methanol or ethanol.
[0034] Beneficial effects: (1) The polyurethane soft segment provided by the present invention is obtained by direct polymerization of carbon dioxide, without the need to utilize DMC, a downstream chemical product of carbon dioxide, thereby contributing to the sustainable development of the polyurethane material industry.
[0035] (2) The polyurethane chain extender provided by the present invention is green in source and low in price, and is a bio-based chain extender, which reduces the dependence of polyurethane materials on petroleum resources;
[0036] (3) In the polyurethane material provided by the present invention, the polycarbonate diol soft segment, the isocyanate unit, and the bio-based chain extender unit containing adjustable high-density hydrogen bonds work synergistically, so that the elastomer material has excellent mechanical properties, and the tensile strength can reach more than 80MPa, which far exceeds the tensile performance index of the average polyurethane elastomer in the market, greatly broadening the application range of the polyurethane elastomer material;
[0037] (4) The preparation method of high-strength polyurethane based on carbon dioxide polycondensation and biomass resources provided by the present invention is simple, suitable for large-scale continuous production, and has good implementation value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 These are stress-strain curves of the tensile test of Example 3 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0039] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0041] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0042] Test instrument model: The universal tensile testing machine used is Instron 5567A.
[0043] Example 1 (the soft segment is PBCDL, and the number average molecular weight is 2000 g / mol) (1) Preparation of chain extender containing oxalamide structure: β-alanine methyl ester hydrochloride (13.96 g, 0.1 mol), triethylamine (20.24 g, 0.2 mol) and 150 mL of anhydrous dichloromethane were placed in a reaction flask, oxalyl chloride (6.35 g, 0.05 mol) was dissolved in 50 mL of anhydrous dichloromethane, and added dropwise to the reaction system at 0°C. After the addition was completed, the temperature was raised to 35°C and the reaction was continued for 8 h. After the reaction was completed, the mixture was washed with water three times, the solvent was removed by rotary evaporation, and the mixture was recrystallized with ethanol to obtain a dimethyl ester compound containing an oxalamide structure. Take a dimethyl ester compound containing an oxalamide structure (7.81 g, 0.03 mol), 80 wt% hydrazine hydrate (4.5 g, 0.072 mol) and 40 mL of ethanol in a reaction bottle, reflux at 80 ° C for 12 h, cool to room temperature after the reaction, filter and wash the filter cake with ethanol three times, and dry to obtain 7.62 g of white powder, i.e., a dihydrazide chain extender containing an oxalamide structure, with a yield of 97.5%.
[0044] (2) Preparation of soft segment: 4.506 g of 1,4-butanediol (50 mmol), 0.0761 g of DBU (0.5 mmol) and 5.679 g of diisopropylcarbodiimide (45 mmol) were placed in a pressure autoclave. High-purity carbon dioxide was introduced into the autoclave to 1 MPa and then the pressure was released to normal pressure. This was repeated three times. Carbon dioxide was then introduced to 1 MPa and the reaction was heated to 130°C for 24 h. After cooling to room temperature, the pressure was released and 15 mL of dichloromethane was added to the system. The filtrate was filtered and washed with 10 mL of 1.0 M hydrochloric acid and 10 mL of deionized water, respectively, and then dried with anhydrous magnesium sulfate. The low molecular weight prepolymer was obtained by suction filtration, rotary evaporation and vacuum drying at 50°C for 12 h. The obtained low molecular weight prepolymer and 0.004g of lithium acetylacetonate were placed in a three-necked flask, the inert gas was replaced three times, and then heated to 200°C and reacted for 1h under mechanical stirring, and the system pressure was slowly reduced to about 50Pa to obtain PBCDL with controllable molecular weight. The number average molecular weight was calibrated to 2000 by nuclear magnetic hydrogen spectrum test.
[0045] (3) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. PBCDL (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and the mixture was vacuumed for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0.008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, a bio-based chain extender containing an oxalamide structure (1.04 g, 0.004 mol) was dispersed in 50 mL DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C and dried for 24 h, and then dried in a vacuum oven at 120 °C for another 24 h to further remove the solvent.
[0046] Example 2 (the soft segment is PBCDL, and the number average molecular weight is 2000 g / mol) (1) Preparation of chain extender containing succinamide structure: β-alanine methyl ester hydrochloride (13.96 g, 0.1 mol), triethylamine (20.24 g, 0.2 mol) and 150 ml of anhydrous dichloromethane were placed in a reaction flask, succinyl chloride (7.75 g, 0.05 mol) was dissolved in 50 ml of anhydrous dichloromethane, and added dropwise to the reaction system at 0°C. After the addition was completed, the temperature was raised to 35°C and the reaction was continued for 8 h. After the reaction was completed, the mixture was washed with water three times, the solvent was removed by rotary evaporation, and the mixture was recrystallized with ethanol to obtain a dimethyl ester compound containing succinamide structure. A dimethyl ester compound containing a succinamide structure (8.65 g, 0.03 mol), 80 wt% hydrazine hydrate (4.5 g, 0.072 mol) and 40 mL of ethanol were placed in a reaction bottle and refluxed at 80 ° C for 12 h. After the reaction was completed, it was cooled to room temperature, filtered and the filter cake was washed three times with ethanol. After drying, 8.24 g of white powder was obtained, i.e., a dihydrazide chain extender containing a succinamide structure, with a yield of 95.2%.
[0047] (2) Preparation of soft segment: the same as (2) in Example 1.
[0048] (3) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. PBCDL (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and the mixture was vacuumed for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0.008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, a bio-based chain extender containing a succinamide structure (1.15 g, 0.004 mol) was dispersed in 50 mL DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C and dried for 24 h, and then dried in a vacuum oven at 120 °C for 24 h to further remove the solvent.
[0049] Example 3 (the soft segment is PBCDL, and the number average molecular weight is 2000 g / mol) (1) Preparation of a chain extender containing a furan dicarboxamide structure: β-alanine methyl ester hydrochloride (13.96 g, 0.1 mol), triethylamine (20.24 g, 0.2 mol) and 150 ml of anhydrous dichloromethane were placed in a reaction flask, 2,5-furan dicarboxylic acid chloride (9.65 g, 0.05 mol) was dissolved in 50 ml of anhydrous dichloromethane, and the mixture was added dropwise to the reaction system at 0°C. After the addition was completed, the temperature was raised to 35°C and the mixture was reacted for 8 h. After the reaction was completed, the mixture was washed with water three times, the solvent was removed by rotary evaporation, and the mixture was recrystallized from ethanol to obtain a dimethyl ester compound containing a furan dicarboxamide structure. A dimethyl ester compound containing a furan dicarboxamide structure (9.79 g, 0.03 mol), 80 wt% hydrazine hydrate (4.5 g, 0.072 mol) and 40 mL of ethanol were placed in a reaction bottle and refluxed at 80 ° C for 12 h. After the reaction was completed, it was cooled to room temperature, filtered and the filter cake was washed three times with ethanol. After drying, 9.42 g of white powder was obtained, i.e., a dihydrazide chain extender containing a 2,5-furan dicarboxamide structure, with a yield of 96.2%.
[0050] (2) Preparation of soft segment: the same as (2) in Example 1.
[0051] (3) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. PBCDL (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and the mixture was vacuumed for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0.008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, a bio-based chain extender containing a furan dicarboxamide structure (1.31 g, 0.004 mol) was dispersed in 50 mL DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C and dried for 24 h, and then dried in a vacuum oven at 120 °C for 24 h to further remove the solvent.
[0052] Example 4 (chain extender is the chain extender in Example 3) (1) Preparation of chain extender: the same as (1) in Example 3.
[0053] (2) Preparation of soft segment: 5.906 g of 1,6-hexanediol (50 mmol), 0.0761 g of DBU (0.5 mmol) and 5.679 g of diisopropylcarbodiimide (45 mmol) were placed in a pressure autoclave. High-purity carbon dioxide was introduced into the autoclave to 1 MPa and then the pressure was released to normal pressure. This was repeated three times. Carbon dioxide was then introduced to 1 MPa and the reaction was heated to 130°C for 24 h. After cooling to room temperature, the pressure was released and 15 mL of dichloromethane was added to the system. The filtrate was filtered and washed with 10 mL of 1.0 M hydrochloric acid and 10 mL of deionized water, respectively, and then dried over anhydrous magnesium sulfate. The low molecular weight prepolymer was obtained by suction filtration, rotary evaporation and vacuum drying at 50°C for 12 h. The obtained low molecular weight prepolymer and 0.005g of lithium acetylacetonate were placed in a three-necked flask, the inert gas was replaced three times, and then heated to 200°C and reacted for 1 hour under mechanical stirring, and the system pressure was slowly reduced to about 50Pa to obtain PHCDL with controllable molecular weight. The number average molecular weight was calibrated to 2000 by nuclear magnetic hydrogen spectrum test.
[0054] (3) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. PHCDL (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and vacuum was applied for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0.008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, a bio-based chain extender containing a furan dicarboxamide structure (1.31 g, 0.004 mol) was dispersed in 50 mL DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C for drying for 24 h, and further dried in a vacuum oven at 120 °C for 24 h to further remove the solvent.
[0055] Example 5 (chain extender is the chain extender in Example 3) (1) Preparation of chain extender: the same as (1) in Example 3.
[0056] (2) Preparation of soft segment: 7.312 g of 1,8-octanediol (50 mmol), 0.0761 g of DBU (0.5 mmol) and 5.679 g of diisopropylcarbodiimide (45 mmol) were placed in a pressure autoclave. High-purity carbon dioxide was introduced into the autoclave to 1 MPa and then the pressure was released to normal pressure. This was repeated three times. Carbon dioxide was then introduced to 1 MPa and the reaction was heated to 130°C for 24 h. After cooling to room temperature, the pressure was released and 15 mL of dichloromethane was added to the system. The filtrate was filtered and washed with 10 mL of 1.0 M hydrochloric acid and 10 mL of deionized water, respectively, and then dried over anhydrous magnesium sulfate. The low molecular weight prepolymer was obtained by suction filtration, rotary evaporation and vacuum drying at 50°C for 12 h. The obtained low molecular weight prepolymer and 0.007g of lithium acetylacetonate were placed in a three-necked flask, the inert gas was replaced three times, and then heated to 200°C and reacted for 1 hour under mechanical stirring, and the system pressure was slowly reduced to about 50Pa to obtain a POCDL with controllable molecular weight. The number average molecular weight was calibrated to 2000 by nuclear magnetic hydrogen spectrum test.
[0057] (3) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. POCDL (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and the mixture was vacuumed for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0.008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, a bio-based chain extender containing a furan dicarboxamide structure (1.31 g, 0.004 mol) was dispersed in 50 mL DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C and dried for 24 h, and then dried in a vacuum oven at 120 °C for 24 h to further remove the solvent.
[0058] Example 6 (chain extender is the chain extender in Example 3) (1) Preparation of chain extender: the same as (1) in Example 3.
[0059] (2) Preparation of soft segment: 8.714 g of 1,10-decanediol (50 mmol), 0.0761 g of DBU (0.5 mmol) and 5.679 g of diisopropylcarbodiimide (45 mmol) were placed in a pressure autoclave. High-purity carbon dioxide was introduced into the autoclave to 1 MPa and then the pressure was released to normal pressure. This was repeated three times. Carbon dioxide was then introduced to 1 MPa and the reaction was heated to 130°C for 24 h. After cooling to room temperature, the pressure was released and 15 mL of dichloromethane was added to the system. The filtrate was filtered and washed with 10 mL of 1.0 M hydrochloric acid and 10 mL of deionized water, respectively, and then dried with anhydrous magnesium sulfate. The low molecular weight prepolymer was obtained by suction filtration, rotary evaporation and vacuum drying at 50°C for 12 h. The obtained low molecular weight prepolymer and 0.008g of lithium acetylacetonate were placed in a three-necked flask, the inert gas was replaced three times, and then heated to 200°C and reacted for 1h under mechanical stirring, and the system pressure was slowly reduced to about 50Pa to obtain a PDeCDL with controllable molecular weight. The number average molecular weight was calibrated to 2000 by nuclear magnetic hydrogen spectrum test.
[0060] (3) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. PDeCDL (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and vacuum was applied for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0 .008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL of DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, a bio-based chain extender containing a furan dicarboxamide structure (1.31 g, 0.004 mol) was dispersed in 50 mL of DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C and dried for 24 h, and then dried in a vacuum oven at 120 °C for 24 h to further remove the solvent.
[0061] Comparative Example 1 (chain extender: adipic acid dihydrazide; soft segment: polytetrahydrofuran dimethanol (PTMG-2000)) (1) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. PTMG-2000 (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120°C, and vacuum was applied for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0.008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL of DMF were added, the temperature was lowered to 85°C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, adipic acid dihydrazide (0.70 g, 0.004 mol) was dispersed in 50 mL of DMF, mixed evenly with the prepolymer, and the reaction was continued at 85°C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80°C and dried for 24 h, and then dried in a vacuum oven at 120°C for 24 h to further remove the solvent.
[0062] Comparative Example 2 (chain extender: the chain extender in Example 3; soft segment: PTMG-2000) (1) Preparation of chain extender: the same as (1) in Example 3.
[0063] (2) Preparation of polyurethane: The reaction was carried out in a three-necked reaction bottle equipped with a mechanical stirrer and a nitrogen inlet and outlet. PTMG-2000 (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and the mixture was vacuumed for 3 h (<100 Pa) to dehydrate. Then, isophorone diisocyanate (IPDI, 1.78 g, 0.008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL of DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Then, a bio-based chain extender containing a furan dicarboxamide structure (1.31 g, 0.004 mol) was dispersed in 50 mL of DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C and dried for 24 h, and then dried in a vacuum oven at 120 °C for 24 h to further remove the solvent.
[0064] Comparative Example 3 (chain extender: adipic acid dihydrazide; soft segment: PBCDL) (1) Preparation of soft segment: the same as (2) in Example 1.
[0065] (2) Preparation of polyurethane: The reaction was carried out in a three-necked reaction flask equipped with a mechanical stirrer and a nitrogen inlet and outlet. PBCDL (8 g, 0.004 mol) was added to the reactor, the oil bath temperature was raised to 120 °C, and vacuum was applied for 3 h (<100 Pa) to dehydrate. Then isophorone diisocyanate (IPDI, 1.78 g, 0 .008 mol), dibutyltin dilaurate (0.0074 g) and 3 mL DMF were added, the temperature was lowered to 85 °C, and the reaction was carried out for 1 h to obtain a prepolymer. Adipic acid dihydrazide (0.70 g, 0.004 mol) was then dispersed in 50 mL DMF, mixed evenly with the prepolymer, and the reaction was continued at 85 °C for 6 h. The polymer solution was cast into a uniform sheet with a thickness of 1-2 mm. The synthesized polymer was then placed in a hot air circulation oven at 80 °C and dried for 24 h, and then dried in a vacuum oven at 120 °C for 24 h to further remove the solvent.
[0066] Comparison table of mechanical properties test of polyurethanes prepared in Examples 1-6 and Comparative Examples 1-3
[0067] Tensile strength (MPa) Elongation at break (%) Example 1 81.6 663.8 Example 2 75.4 738.6 Example 3 85.2 671.8 Example 4 78.7 864.8 Example 5 74.5 785.6 Example 6 72.0 774.7 Comparative Example 1 42.1 1365.3 Comparative Example 2 56.4 1370.1 Comparative Example 3 69.6 876.22
[0068] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent structure or equivalent process transformation made by using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the protection scope of the present invention.
Claims
1. A type of high-strength polyurethane based on carbon dioxide polycondensation, characterized in that: The raw material components include polycarbonate diol, diisocyanate, catalyst and chain extender; Wherein, in terms of molar fractions, the diisocyanate is 100 parts; the catalyst is 0.05-0.5 parts; the sum of the polycarbonate diol and the chain extender is 100 parts, and the chain extender is 25-50 parts; The chain extender structure is: Where n=0, 1; The catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, stannous isooctanoate, phosphoric acid, oleic acid, adipic acid and triethylamine.
2. The high-strength polyurethane based on carbon dioxide polycondensation according to claim 1, characterized in that: The diisocyanate is selected from at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, lysine diisocyanate, 1,4-cyclohexane diisocyanate and toluene diisocyanate.
3. The high-strength polyurethane based on carbon dioxide polycondensation according to claim 1, characterized in that: The number average molecular weight of the polycarbonate diol is 800-2000 g / mol.
4. The high-strength polyurethane based on carbon dioxide polycondensation according to claim 1, characterized in that: The polycarbonate diol is prepared by the following method: R1. Dehydration polycondensation of carbon dioxide and aliphatic diol: aliphatic diol, organic base catalyst and carbodiimide compound are placed in a pressure-resistant autoclave, heated to 130° C. in a carbon dioxide atmosphere at 1 MPa for dehydration polycondensation, reacted for 6-24 hours, and then post-treated to obtain oligocarbonate; R2, melt polycondensation of oligocarbonate: the oligocarbonate prepared in step R1 and the polycondensation catalyst are placed in a reactor, heated to 160-230° C. under an inert gas atmosphere and mechanical stirring, and then the pressure is reduced to 50-200 Pa for melt polycondensation, and the reaction is carried out for 0.5-1 h to obtain the polycarbonate diol; The structural formula of the aliphatic diol is: Among them, n=2, 3, 4, 5.
5. The organic base catalyst is selected from at least one of N,N,N',N'-tetramethylethylenediamine, 4-dimethylaminopyridine, 4-pyrrolidinylpyridine, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5,7-triazabicyclo[4.4.0]decene-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,1,3,3-tetramethylguanidine and 2-tert-butyl-1,1,3,3-tetramethylguanidine; The carbodiimide compound is selected from at least one of dicyclohexylcarbodiimide and diisopropylcarbodiimide.
6. The high-strength polyurethane based on carbon dioxide polycondensation according to claim 4, characterized in that: In the preparation method of polycarbonate diol, the polycondensation catalyst is at least one of sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide, lithium acetylacetonate, zirconium acetylacetonate and cesium carbonate.
7. The high-strength polyurethane based on carbon dioxide polycondensation according to claim 4, characterized in that: The mass ratio of the oligomeric carbonate to the polycondensation catalyst is 1:(0.001-0.005).
8. A method for preparing high-strength polyurethane based on carbon dioxide polycondensation according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, adding polycarbonate diol into a reactor, and heating and dehydrating under vacuum; S2, under the protection of inert gas, adding diisocyanate, catalyst and solvent to react to obtain a prepolymer; S3. Under the protection of inert gas, the chain extender and the solvent are mixed and added into a reactor to carry out a chain extension reaction; thereafter, the mixture is poured, solidified and dried to obtain the high-strength polyurethane based on carbon dioxide polycondensation.
9. The method for preparing high-strength polyurethane based on carbon dioxide polycondensation according to claim 7, characterized in that: The solvent is selected from at least one of toluene, xylene, acetone, dichloromethane, chloroform, tetrahydrofuran, acetonitrile, ethyl acetate, butyl acetate, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
10. The method for preparing high-strength polyurethane based on carbon dioxide polycondensation according to claim 7, characterized in that: The amount of the solvent added in step S2 is 3-10 times the amount of the diisocyanate substance; the amount of the solvent added in step S3 is 30-100 times the amount of the diisocyanate substance.
11. The method for preparing high-strength polyurethane based on carbon dioxide polycondensation according to claim 7, characterized in that: In step S1, the vacuum degree is less than 200Pa, the heating temperature is 90-120°C, and the dehydration time is 1-6h; in step S2, the heating temperature is 80-100°C, and the prepolymerization time is 1-3h; in step S3, the heating temperature of the chain extension reaction is 50-100°C, and the reaction time is 4-12h; the pouring and curing temperature is 80-120°C, and the pouring and curing time is 24-48h.
Citation Information
Patent Citations
Polycarbonate type polyurethane elastomer sealing material as well as preparation method and application thereof
CN113461905A
Polyurethane rubber and preparation method thereof
CN116622216A
Organosilicon-modified aqueous polyurethane-acrylate composite coating agent and preparation method thereof
CN102559031A
High-silicon-content organic silicon-polyurethane-acrylate composite coating agent and preparation method thereof
CN102585650A
Coating compositions for glass substrates
WO2011022055A2
Cited By
High-strength and high-draw-ratio bio-based polyurethane elastomer and preparation method thereof
CN117343260A
Bio-based polyurethane elastomers with high strength and high tensile ratio and methods of making the same
CN117343260B